2021
DOI: 10.1007/s13202-021-01409-6
|View full text |Cite
|
Sign up to set email alerts
|

Experimental study on the performance of emulsions produced during ASP flooding

Abstract: ASP (Alkaline/Surfactant/Polymer) flooding is one of the most promising techniques that has proven to have successful application in several laboratory and pilot tests. However, the formation of persistent and stable emulsions is one of the associated problems with ASP flooding. The present work investigated the effect of sodium carbonate alkaline, Alpha Olefin Sulfonate (AOS) surfactant, and GLP100 polymer on produced crude oil emulsion. The study was conducted by measuring the emulsion stability in terms of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(5 citation statements)
references
References 56 publications
0
5
0
Order By: Relevance
“…It was seen from the Coehen rule that, among the two substances in contact with each other, the substance with the larger dielectric constant was positively charged. 20 Therefore, the water phase was positively charged. According to the Schulze–Hardy rule, the ions with opposite charges to the dispersed droplets had the effect of demulsification 21 The higher the valence, the better the demulsification effect.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It was seen from the Coehen rule that, among the two substances in contact with each other, the substance with the larger dielectric constant was positively charged. 20 Therefore, the water phase was positively charged. According to the Schulze–Hardy rule, the ions with opposite charges to the dispersed droplets had the effect of demulsification 21 The higher the valence, the better the demulsification effect.…”
Section: Resultsmentioning
confidence: 99%
“…The results of studies on the stability of surfactant emulsions and demulsification showed that the generation of crude oil emulsions was not conducive to subsequent refining and transportation of crude oil. 20 While the generation process of the emulsion was relatively complicated in actual production, as a result, the oil–water emulsion in crude oil must be treated with non-ionic surfactants on the basis of the physical method to achieve efficient oil–water separation. Some experiments have been carried out on the preparation and generation factors of emulsions, and tiny oil–water emulsions were prepared by the shearing method.…”
Section: Introductionmentioning
confidence: 99%
“…Microscopy helps in observing the dispersed droplets having a size smaller than 100 μm . Imaging techniques such as cross polarized microscopy, fluorescence microscopy, and cryo-based scanning electron microscopy are some of the techniques that are used to study droplet structure. In terms of precision and detail, electron microscopes such as field emission electron microscopes and transmission electron microscopes are the best choice for this purpose due to their high resolution and ability to capture large surface area images quickly. Given the sample has to be frozen, comparatively the high resolution is most suitable for analyzing individual droplet shape, size, and morphology as well as the distribution of droplets throughout the emulsion and at the interface. , Combining microscopic imaging with a more precise droplet size distribution (DSD) technique such as a light scattering-based or acoustic-based technique further strengthens surety regarding the droplet structural features and stability of the emulsion.…”
Section: Emulsion Characteristics and Measuring Techniquesmentioning
confidence: 99%
“…For instance, studies conducted by Belhaj et al demonstrated an optimized formulation of alkyl ether carboxylate and alkylpolyglucoside (50:50) could tolerate high temperature and salinity levels (Belhaj, Elraies, et al, 2020; Belhaj, Shuhli, et al, 2020). Additionally, the recent advances encompassed the investigation of surfactant applications in tight rock reservoirs and surfactant loss during the injection process (Belhaj, Elraies, Alnarabiji, et al, 2021; Belhaj, Elraies, Sarma, et al, 2021; Laben et al, 2022; Liang et al, 2021). However, traditional surfactants, which have been at the forefront of chemical oil recovery efforts, often struggle to maintain stability and efficacy under harsh reservoir conditions characterized by elevated temperatures and high salinity levels.…”
Section: Introductionmentioning
confidence: 99%